Learning, judgement and workforce tensions impact failure to fail in a medical postgraduate setting: A supervisor perspective. (3rd October 2022) - Daly, Michele; Lucas, Gillian; Wilkinson, Tim J.
Abstract: Purpose: Medical training organisations have a duty to prepare medical graduates for future safe, competent practice. Decisions about underperformance are high stakes at the postgraduate level and failure to fail can occur. We aimed to explore this concept from a systems and supervisor perspective. Method: Supervisors of specialist physician trainees were invited to provide written feedback on failure to fail as part of a broader anonymous supervisor survey. They were provided with a trigger statement and responded in free-text format. A deductive content analysis was undertaken through the lenses of supervisor and institution. Results: Of 663 supervisors who responded to the broader survey, 373 (56%) provided feedback on the failure to fail trigger statement. Analyses indicated an interplay between trainee and supervisor characteristics, and broader system elements. System elements that contributed to failure to fail trainees included lack of longitudinal monitoring and quality of assessment information. Supervisor characteristics included confident, conflicted and avoidant behaviours towards underperforming trainees. Conclusions: Individual and system challenges that contributed to failure to fail were identified in this study, and we propose a three-way tension among learning, judgement and workforce. Three potential mitigation strategies have been identified to reduce failure to fail, namely a stage-based approach to remediation, faculty development in supervisory skills and improved assessment-for-learning processes.